2019
DOI: 10.1002/ese3.533
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of in situ stress and its influence on coalbed methane development: A case study in the eastern part of the southern Junggar Basin, NW China

Abstract: Based on 54 sets of well test data of 29 coalbed methane (CBM) wells, the distribution characteristic of in situ stress in the eastern part of the southern Junggar Basin and its control on permeability (K), reservoir pressure (P o ), and gas content (G) were discussed systematically. The results show that three types of in situ stress regime exist and are converted corresponding to a certain depth, (1) <600 m is the strike-slip fault regime (σ H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The seepage pressure was always less than the confining pressure to prevent water from flowing out between the heat‐shrinkable tube and the specimen. These test conditions were selected because, according to the actual in situ stress conditions and empirical formula in the study area, the horizontal in situ stress is approximately 10–20 MPa, and the seepage pressure is approximately 3 MPa within the depth range of the sample used in the test 35–37 . Different confining pressures and seepage pressures were selected to simulate different depth effects, and enough test data were obtained to understand the permeability evolution process of sandstone under different confining and seepage pressures.…”
Section: Equipment and Methodsmentioning
confidence: 99%
“…The seepage pressure was always less than the confining pressure to prevent water from flowing out between the heat‐shrinkable tube and the specimen. These test conditions were selected because, according to the actual in situ stress conditions and empirical formula in the study area, the horizontal in situ stress is approximately 10–20 MPa, and the seepage pressure is approximately 3 MPa within the depth range of the sample used in the test 35–37 . Different confining pressures and seepage pressures were selected to simulate different depth effects, and enough test data were obtained to understand the permeability evolution process of sandstone under different confining and seepage pressures.…”
Section: Equipment and Methodsmentioning
confidence: 99%
“…The permeability includes matrix permeability and fracture system permeability; the former is almost negligible, and the latter is the main factor to control the percolation conditions of the coal reservoir [44]. Permeability is mainly affected by geological factors such as stress field, burial depth, coal structure, and fractures [5,45].…”
Section: Permeability Variation With Depthmentioning
confidence: 99%
“…In situ stress is a type of internal stress in the Earth's crust, which is mainly controlled by gravity and tectonic activity [1][2][3][4][5]. Permeability is one of the important factors affecting the efficiency of coalbed methane (CBM) production.…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of coal properties, Wang et al (2018) and Zhang T et al (2021) studied the permeability anisotropy of high-dipping coals from the southern Junggar Basin based on laboratory experiments and numerical simulations. Li et al (2019) and Fu et al (2020) reported several datasets of in-situ stress from the eastern part of the southern Junggar Basin and discussed vertical permeability trends. Zhou et al (2016) and Li et al (2017) conducted experimental studies on the pore structure characteristics of coals in the southern Junggar Basin.…”
Section: Introductionmentioning
confidence: 99%